Polyphenols affect the humoral response in cancer, infectious and allergic diseases and autoimmunity by modulating the activity of TH1 and TH2 cells. (October 2021) - Benvenuto, Monica; Focaccetti, Chiara; Ciuffa, Sara; Fazi, Sara; Bei, Arianna; Miele, Martino Tony; Albonici, Loredana; Cifaldi, Loredana; Masuelli, Laura; Bei, Roberto
Abstract: Polyphenols are a wide class of natural substances, pleiotropic molecules capable of modulating several processes, involved in the humoral and cellular immune response. The activation, differentiation of B cells, and production of antibodies to protein antigens by plasma cells depend on T helper (TH ) CD4 + cells and secreted cytokines. Cancer, infectious, allergic, and autoimmune diseases are characterized by an imbalance of TH 1/TH 2 immunity and abnormal activation of the humoral response. Accordingly, polyphenols modulate the TH 1/TH 2 ratio, the secretion of multiple cytokines, the levels of antibodies, and therefore could contribute to recovering the state of health in these diseases. In this review, we summarize the current knowledge on the effects of polyphenols in modulating the humoral response in cancer, infectious and allergic diseases and in autoimmunity by affecting the activity of TH 1 and TH 2 cells.